Gender disparities in the association between atherogenic index of plasma and chronic kidney disease - Yong Wang; Jing Cui; Jing Gao; Shuang Liang; Guangyan Cai; Xiangmei Chen (BMC Public Health)
Abstract Objective This study investigates the relationship between the atherogenic index of plasma (AIP) and chronic kidney disease (CKD) occurrence in the general population, with a focus on potential gender disparities. Methods The study included 22,952 adults from the National Health and Nutrition Examination Survey (NHANES). Various statistical models were employed to evaluate the association between AIP and CKD occurrence and explore gender-specific differences. Results Adjusted for confounding factors, higher AIP levels showed a mild association with increased CKD risk in the general population. Specifically, individuals in the highest AIP quartile had a slightly elevated odds ratio (OR) for CKD compared to the lowest quartile (OR: 1.24, 95% CI: 1.02–1.52, P for trend = 0.023). Gender-stratified analysis revealed significant differences. Among males, higher AIP levels were significantly associated with CKD risk (OR: 1.49, 95% CI: 1.15–1.94, P for trend < 0.001), whereas in females, the association was weaker and statistically non-significant (P for trend = 0.055). U-shaped relationships between AIP and CKD were observed. Mediation analysis provided insights into potential pathways underlying this association. Among males, changes in uric acid accounted for 44.50% of CKD prevalence related to AIP, while glomerular filtration rate (eGFR), BMI, and bicarbonate levels contributed 44.09%, 17.55%, and 15.36%, respectively. Among females, uric acid changes accounted for 45.53%, while eGFR, bicarbonate, C-reactive protein (CRP), sodium, and potassium levels contributed 37.96%, 12.43%, 6.37%, 5.58%, and 3.14%, respectively. Conclusion Our findings suggest that elevated AIP levels may increase CKD risk, particularly among males in the general U.S. population.